mGlu5 Receptor Functional Interactions and Addiction - Brown, Robyn; Mustafa, Sanam; Ayoub, Mohammed; Dodd, Peter; Pfleger, Kevin; Lawrence, Andrew (Frontiers in Pharmacology, 2012)
The idea of “receptor mosaics” is that proteins may form complex and dynamic networks with respect to time and composition. These have the potential to markedly expand the diversity and specificity of G protein-coupled receptors (GPCR) signaling, particularly in neural cells, where a few key receptors have been implicated in many neurological and psychiatric disorders, including addiction. Metabotropic glutamate type 5 receptors (mGlu5) can form complexes with other GPCRs, including adenosine A2A and dopamine D2 receptors. mGlu5-containing complexes have been reported in the striatum, a brain region critical for mediating the rewarding and incentive motivational properties of drugs of abuse. mGlu5-containing complexes and/or downstream interactions between divergent receptors may play roles in addiction–relevant behaviors. Interactions between mGlu5 receptors and other GPCRs can regulate the rewarding and conditioned effects of drugs as well as drug-seeking behaviors. mGlu5 complexes may influence striatal function, including GABAergic output of striatopallidal neurons and glutamatergic input from corticostriatal afferents. Given their discrete localization, mGlu5-[non-mGlu5] receptor interactions and/or mGlu5-containing complexes may minimize off-target effects and thus provide a novel avenue for drug discovery. The therapeutic targeting of receptor–receptor functional interactions and/or receptor mosaics in a tissue specific or temporal manner (for example, a sub-population of receptors in a “pathological state”) might reduce detrimental side effects that may otherwise impair vital brain functions.